Analysis of health risk factors for older adults living alone in China and establishment and evaluation of a nomogram prediction model - Chen, Kexin; Qiu, Jiangwei; Wang, Wenlong; Hu, Qi; Qiao, Hui (Frontiers in Public Health, 2024)
To understand the health status of the elderly living alone in China and analyze the influencing factors, so as to provide reference for improving the health status of the elderly living alone. Methods: Based on CGSS data from China General Social Survey (2017), the influencing factors of health status of elderly living alone were analyzed by unconditional Logistic regression, and the R software was used to develop a nomogram for predicting the risk of self-assessed unhealthy adverse outcomes. Results: Gender, annual income, mandarin listening level and participation in medical insurance were the influencing factors of self-rated health of elderly living alone. Age and annual income are the influencing factors of physiological health. Annual income and Internet use were influential factors for mental health. C-Statistic of nomogram prediction model was 0.645. The calibration curve showed that goodness of fit test ( χ 2 = 58.09，P<0.001 ), and the overall prediction ability of the model was good.The health status of the elderly living alone in the home-based elderly care is worrying, and it is affected by various factors. We should pay more attention to the elderly living alone, improve the ability of listening and distinguishing mandarin and the use of health information platforms for the elderly living alone, and further implement medical insurance policies and health services. Announcing the solution to promote healthy home-based care for the elderly living alone.